Idol. - Raab Galerie, Berlin; Kunsträume Köln; Raab, Ingrid; Hannesen, H.- Gerhard (Berlin : Raab Galerie Berlin, 1985)
Albert, Hermann ; Bach, Elvira ; Campbell, Steven ; Castelli, Luciano ; Chevalier, Peter ; Fetting, Rainer ; Goller, Bruno ; Heidacker, Stephanus ; Kaminski, Max ; Klossowski, Pierre ; Kögler, Harry ; McKenna, Stephen ; Salomé ; Schindler, Thomas ; Weishaupt, Andreas ; Zimmer, Bernd
Idol, Raab Galerie, Berlin, 6.11. - 30.12.1985 / Kunsträume Köln, 10.11. - 30.11.1985
biografie
Duits & Engels
boek